Pendekar Siber portal: empowering Malaysian youth through cybersecurity education - Ismail, Nur Syafini; Ismail, Siti Aisyah; Abdul Molok, Nurul Nuha (KICT Publishing, 2024)
The rise of digitalization and interconnected environment has made cyber threats more prevalent today. To address these threats, organizations need cybersecurity experts to defend their information systems from cyber-attacks. Hence, Malaysia is in need of 30,000 cybersecurity knowledge workers by 2030. To address this critical need, the Pendekar Siber initiative was created to build Malaysia's cybersecurity capability by educating and recruiting youth to become a pendekar siber (cyber warrior, defender of the cyber realm). The program utilizes a sustainable train-the-trainer model, ensuring that trained individuals can further train their peers, thus expanding the reach and impact of cybersecurity education. The initiative includes the development of a comprehensive online platform designed to not only enhance cybersecurity awareness among young people but also to spark their passion for cybersecurity and inspire them to pursue a career in the field. This portal features cybersecurity training modules, discussion forums, personality tests, and cybersecurity career information. It was developed using Agile software development principles and used vxjs, visual studio, node.js and mongodb to develop the web portal.